A Nonrandomized Trial of Prolonged Exposure and Cognitive Processing Therapy for Combat-Related Posttraumatic Stress Disorder in a Deployed Setting. Issue 6 (November 2020) - Peterson, Alan L.; Foa, Edna B.; Resick, Patricia A.; Hoyt, Timothy V.; Straud, Casey L.; Moore, Brian A.; Favret, James V.; Hale, Willie J.; Litz, Brett T.; Rogers, Timothy E.; Stone, Jay M.; Villarreal, Robert; et al.
Abstract: For many decades, the U.S. military's general operational guideline has been to limit the use of trauma-focused treatments for combat and operational stress reactions in military service members until they have returned from deployment. Recently, published clinical trials have documented that active-duty military personnel with combat-related posttraumatic stress disorder (PTSD) can be treated effectively in garrison. However, there are limited data on the treatment of combat and operational stress reactions or combat-related PTSD during military deployments. This prospective, nonrandomized trial evaluated the treatment of active-duty service members ( N = 12) with combat and operational stress reactions or combat-related PTSD while deployed to Afghanistan or Iraq. Service members were treated by deployed military behavioral health providers using modified Prolonged Exposure (PE; n = 6) or modified Cognitive Processing Therapy (CPT; n = 6), with protocol modifications tailored to individual mission requirements. The PTSD Checklist–Military Version (PCL-M) total score was the primary outcome measure. Results indicated that both groups demonstrated clinically significant change in PTSD symptoms as indicated by a reduction of 10 points or greater on the PCL-M. Participants treated with modified PE had significant reductions in PTSD symptoms, t = -3.83, p = .01; g = -1.32, with a mean reduction of 18.17 points on the PCL-M. Participants treated with modified CPT had a mean PCL-M reduction of 10.00 points, but these reductions were not statistically significant, t = -1.49, p = .12; g = -0.51. These findings provide preliminary evidence that modified forms of PE and CPT can be implemented in deployed settings for the treatment of combat and operational stress reactions and combat-related PTSD. Highlights: Few studies have evaluated trauma-focused treatments for PTSD during deployments. This study evaluated the use of PE and CPT for PTSD during a military deployment. Twelve deployed U.S. military service members were treated with PE or CPT. Both treatments demonstrated clinically significant reductions in PTSD symptoms. Modified forms of PE and CPT can be used effectively in deployed settings.